2014
DOI: 10.1007/s00464-014-4037-1
|View full text |Cite
|
Sign up to set email alerts
|

Total inverse transgastric resection with transoral specimen removal

Abstract: Gastric GIST should be resected laparoscopically if negative margins are safely achieved regardless of its size. Tumors at the frontwall and exophytic backwall GIST are addressed by laparoscopic wedge resection. Tumors at the gastrojejunal junction, in the prepyloric region, and fundus as well as submucous GIST of the gastric backwall are best approached by intragastric laparoscopic resection. Transoral specimen retrieval is an interesting option in smaller tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…With the concept and advances in LECS [ 7 , 8 , 9 , 10 , 11 ] by a multidisciplinary team, we modified and simplified the backup surgery after endoscopic resection [ 31 ] regardless of tumor location. Although a previous retrospective study demonstrated that laparoscopic wedge resection could also treat tumors in an unfavorable location in the lesser curvature or the posterior wall of the gastric body, fundus, and antrum [ 32 ], different methods with endoscopic submucosal tunneling [ 18 ], laparoscopic transgastric approach [ 32 , 33 ], and anatomic gastrectomy [ 34 ] have been reported to avoid lumen stenosis in tumors located near the gastroesophageal junction or the prepyloric area. In our study, once the tumor was easily identified after incomplete ER, the surgeon completed resection using a laparoscopic stapling device and adjusted to the transverse direction of the stomach in the junction area to minimize the resected volume and preserve the greatest function.…”
Section: Discussionmentioning
confidence: 99%
“…With the concept and advances in LECS [ 7 , 8 , 9 , 10 , 11 ] by a multidisciplinary team, we modified and simplified the backup surgery after endoscopic resection [ 31 ] regardless of tumor location. Although a previous retrospective study demonstrated that laparoscopic wedge resection could also treat tumors in an unfavorable location in the lesser curvature or the posterior wall of the gastric body, fundus, and antrum [ 32 ], different methods with endoscopic submucosal tunneling [ 18 ], laparoscopic transgastric approach [ 32 , 33 ], and anatomic gastrectomy [ 34 ] have been reported to avoid lumen stenosis in tumors located near the gastroesophageal junction or the prepyloric area. In our study, once the tumor was easily identified after incomplete ER, the surgeon completed resection using a laparoscopic stapling device and adjusted to the transverse direction of the stomach in the junction area to minimize the resected volume and preserve the greatest function.…”
Section: Discussionmentioning
confidence: 99%
“…These approaches include tumor enucleation, exogastric wedge resection, transgastric tumor-everting resection, intragastric tumor everting resection, laparoscopic and endoscopic cooperative surgery and esophagogastrectomy [8][9][10][11] .…”
Section: Discussionmentioning
confidence: 99%
“…If the gastric wall is the abdominal wall, EATR is an open surgery, LIGS is a laparoscopic surgery, and SI-IGR is a single-port laparoscopic surgery [ 2 26 27 ]. In the case of SI-IGR, because there are no obstacles in trocar insertion and fixation (in contrast to LIGS), it can be performed quicker and more conveniently.…”
Section: Lecs Procedures For Benign Gastric Tumorsmentioning
confidence: 99%